The Effect of Financial Literacy on Cryptocurrency Investment Intention: The Mediating Role of Perceived Risk - Vidya Ramadhan Putra Pratama (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study examines the effect of financial literacy on cryptocurrency investment intention and tests whether perceived risk mediates the relationship. A quantitative cross-sectional survey was conducted among 40 active cryptocurrency investors in Indonesia. The model was estimated using variance-based Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.29. The measurement model satisfied reliability, convergent validity, and discriminant validity requirements. The structural model shows that financial literacy has a positive and significant effect on investment intention (β = 0.700; p < 0.001) and, unexpectedly, also has a positive and significant effect on perceived risk (β = 0.703; p < 0.001). Perceived risk does not significantly affect investment intention (β = 0.003; p = 0.495), and the indirect effect of financial literacy through perceived risk is insignificant (β = 0.002; p = 0.495). These findings indicate that financially literate crypto investors may recognize more risks without becoming less willing to invest. Accordingly, financial literacy may operate primarily as a decision-enabling and risk-recognition capability rather than through a risk-reduction mechanism. The study contributes to the literature by distinguishing risk awareness from risk avoidance among active cryptocurrency investors and highlights the need for investor education that emphasizes risk-management competence.